Pengaruh Pertumbuhan Penduduk Dan Dependency Ratio Terhadap Pertumbuhan Ekonomi Di Provinsi Aceh - Sarinah; labita, farah (Jurnal Samudra Ekonomika, 2024)
This research aims to determine the effect of population growth and dependency ratio on economic growth in Aceh Province. The data used is data on population growth, dependency ratio, and economic growth in Aceh Province, where the data used is time series data for the 2017-2022 period obtained from BPS Aceh Province. The data analysis method uses multiple linear regression analysis, t test, F test, and coefficient of determination test. The regression equation in this research is Y = 3.188 + 0.445X1 + 0.319X2. From the data analysis it can be explained that population growth has a significant effect on the economic growth of Aceh Province. Dependency ratio has a significant effect on the economic growth of Aceh Province. Population growth and dependency ratio simultaneously have a significant effect on the economic growth of Aceh Province. The variables population growth and dependency ratio influence the economic growth of Aceh Province by 49.1%, while the remaining 50.9% is influenced by other variables not examined in this research.